The glass eel : a novel - Viertel, J. J. (The Mysterious Press, 2025)
"Caterpillar Island, off the coast of Maine, hides a dark underworld of baby eel smuggling, fast cash, and violent trade under its idyllic surface. Jeanette King, a hard-working divorcée, is pulled into this dangerous scene when her ex-husband becomes entangled in the elver trade. With help from a local cop and an Indigenous activist, she navigates a web of crime, community, and environmental peril." --